Influence of Stigma and Shame on HIV Screening among Women in Prostitution (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
Background: Shame and stigma brings about undesirable attribute and significantly contributes to the HIV screening and STI treatment seeking, particularly among sex workers. Societal compulsion and feelings of perceived stigma and shame make the sex workers more vulnerable and likely to destabilize their community and the community at large, if no attention is paid. Hence this study was necessitated to document the experiences of stigma and shame and its influence in HIV screening. Methods: This descriptive research was conducted among commercial sex workers (CSW) enlisted by a NGO. Using simple random sampling procedure research team has interviewed 58 respondents. Semi structured interview schedule was used to explore the knowledge, sexuality, experience of shame and stigma. Michigan Alcohol Screening Test brief scale was used to assess alcohol dependence. Written informed consent was obtained from participants prior to data collection. Results: Rates of shame and stigma were high among the study participants. Income, knowledge of HIV, alcohol dependence, and number of partners, access to pornographic films, history of sexually transmitted infections (STI) and shame was independently associated with HIV screening. However, marital status of the respondents was inversely related to HIV screening. Conclusions: Experience of shame associated with the profession was so intense among CSW. This experience of shame acts as a barrier in getting screened for HIV while stigma may not be a powerful barrier. Key words: Sex worker; Stigma and Shame; HIV screening DOI: 10.3126/saarctb.v5i2.3071 SAARC J. Tuber. Lung Dis. HIV/AIDS 2008 Vol.5(2) 15-21